Beginnings: An Introduction to Form Generation (Oz, 1990)
Work from Studio 319 Willard Isao Ameku, Scott Arford, Mark .Barnes, Michael (Odie) Deane, Amy Foster, Kevin Heath , Lara Jenkins, Mim Jitchell, John Nelson , Geffrey Ortiz-Gass, Tim Schinsky, Doug Shaffer, Bill Singer, and Bryan Zimmer. Beginnings The question of beginning is a profound one in design. I believe we are all victims of our process. The point of departure (i.e. the beginning) predicts one's design. The process, in tum, becomes a self-fulfilling prophecy.